The Role of cultural identity in the relationship between physical exercise and psychological abnormality of college students from an Ideological and political perspective - Wei Sun (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study aims to determine, from the ideological and political education perspective, the function of ethnic and cultural identity in the relationship between physical exercise and psychological abnormality. Multifactor variance is used to measure physical activity, ethnic, cultural identity, and psychological abnormality from the perspective of ideological and political education of college students. Results: The results indicate that the main effect of exercise cultural attributes is highly significant, F=3.090, p<0.01, whereas the interaction between exercise volume, exercise cultural attributes, and exercise volume is not significant. Enhancing ethnic and cultural identity can reduce the incidence of mental disorders. Important predictors of the severity of psychological abnormalities include the duration of physical activity and ethnic and cultural identity. Ideological and political education and mental health education are continuously expanding, and due to the incremental growth of quality education, specifics have changed gradually.